Engaging with barriers hampering uptake of digital tools - Mikelis Grivins; Emils Kilis (Italian Review of Agricultural Economics (REA), 2023)
It is widely accepted that digitalisation can allow us to tackle the social, economic and even environmental challenges that agro-food systems are currently facing. There is a vibrant debate regarding the challenges one might face when adopting digital tools. This article engages in this discussion by exploring how barriers farmers encounter when implementing digital solutions manifest themselves as practical challenges farmers have to resolve. To do this, the article explores three cases in Latvia's beef farming sector. The article focuses on the following two questions: 1) what were the challenges that the groups of farmers faced while trying to implement the new solutions; 2) how did these challenges transform the initial solutions the farmers were trying to implement? The three cases represent three initiatives at various stages of development (an emerging cooperative of beef farmers; an unorganised attempt by farmers to develop joint digital marketing tools; an online shop developed and maintained by an individual enterprise). The article argues that there are multiple creative strategies for dealing with barriers to digitalisation, but studies focusing on different obstacles to digitalisation should also be mindful of pre-existing issues that hamper digitalisation, while simultaneously being impervious to purely digital fixes.
Keywords: Q1; M31; O18; 330; barriers; beef sector; digital tools; rural development